2005
DOI: 10.1007/s10517-005-0337-8
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Cellular Stimulation of Thyroid Transplant for Correction of Thyroid System Function

Abstract: The efficiency of autotransplantation of the thyroid tissue into the greater omentum was demonstrated in experiments on rats. High viability of the transplant and restoration of the hormonal thyroid activity were attained after a single injection of the cell suspension of autologous adherent bone marrow cells directly into the transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Approximately eight in vivo studies exist between 1981 and 2022 [117][118][119][120][121][122][123]. In these studies on thyroid transplantation; auto-and allotransplantation of irradiated thyroid tissue in rats with syngenic rats have been evaluated.…”
Section: Thyroid Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately eight in vivo studies exist between 1981 and 2022 [117][118][119][120][121][122][123]. In these studies on thyroid transplantation; auto-and allotransplantation of irradiated thyroid tissue in rats with syngenic rats have been evaluated.…”
Section: Thyroid Transplantationmentioning
confidence: 99%
“…That in vivo study has a significant role in stem cell and thyroid transplantation [119]. Furthermore, a different study reported the greater omentum feasibility as a transplant site for thyroid tissue via in vivo auto-transplantation model [120]. A more recent study from Wiseman et al described a cell-pouch system for the thyroid tissue and determined the efficiency with viability and thyroid functionality after the subcutaneous transplantation model [121].…”
Section: Thyroid Transplantationmentioning
confidence: 99%
“…The efficiency of transplantation of hemopoietic precursors isolated from the blood is higher than that of bone marrow cells [9,14]. Experimental data indicate that MSC mobilized by means of cytokine preparations possess therapeutic activity in situ in some disease, e. g. in myocardial infarction [1,17,18]. All these data indicate that methods of noninvasive manipulations with endogenous stem cells deserve special attention.…”
mentioning
confidence: 99%
“…On the other hand, new methods for mobilization of the recipient own bone marrow mesenchymal stem cells (MSC) by injection of specific mobilization factors, e. g. granulocytic CSF (G-CSF) and stem cell factor, are intensively developed now. Positive results of preventive and therapeutic injections of these factors to animals with experimental myocardial infarction were reported [2,12,13].…”
mentioning
confidence: 99%